2021
DOI: 10.1080/13674676.2021.1871595
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Francis Owl-Lark Indices (FOLI): assessing the implications of diurnal activity patterns for clergy work-related psychological health

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The more recent of the two measures, the Francis Burnout Inventory (Francis et al, 2005 ) was designed specifically for use among religious professionals and clergy and has been employed in a diverse range of studies, including work reported by Francis et al ( 2008 ), Francis et al ( 2009 ), Robbins and Francis ( 2010 ), Brewster et al ( 2011 ), Francis et al ( 2012 ), Robbins et al ( 2012 ), Barnard and Curry ( 2012 ), Randall ( 2013a , 2013b , 2015 ), Francis et al ( 2013a , 2013b , 2013c ), Robbins and Francis ( 2014 ), Francis et al ( 2015 ), Sterland ( 2015 ), Francis and Crea ( 2015 ), Durkee-Lloyd ( 2016 ), Francis and Crea ( 2018 , 2021 ), Francis et al ( 2019a ) and Francis et al ( 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…The more recent of the two measures, the Francis Burnout Inventory (Francis et al, 2005 ) was designed specifically for use among religious professionals and clergy and has been employed in a diverse range of studies, including work reported by Francis et al ( 2008 ), Francis et al ( 2009 ), Robbins and Francis ( 2010 ), Brewster et al ( 2011 ), Francis et al ( 2012 ), Robbins et al ( 2012 ), Barnard and Curry ( 2012 ), Randall ( 2013a , 2013b , 2015 ), Francis et al ( 2013a , 2013b , 2013c ), Robbins and Francis ( 2014 ), Francis et al ( 2015 ), Sterland ( 2015 ), Francis and Crea ( 2015 ), Durkee-Lloyd ( 2016 ), Francis and Crea ( 2018 , 2021 ), Francis et al ( 2019a ) and Francis et al ( 2021b ).…”
Section: Introductionmentioning
confidence: 99%